Digital Media as a Boundless World: A Social Hermeneutic Study - David Octovianus Roos; Fresal Arthur Sopamena (Univiversitas Dr. Djar Wattiheluw, 2025)
This study examines the significant role of digital media as a limitless space that transforms meaning and social interaction in modern society. Through a social hermeneutic approach, it explores how technology and information media transcend physical and social boundaries, creating a dynamic and complex communication environment. Digital media eliminates spatial and temporal limits, enabling instant, global information exchange and interaction. However, this openness also requires critical awareness and ethical communication to address issues such as misinformation, multiple interpretations, and conflicts in meaning. By understanding these dynamics, society can use digital media more wisely to build effective, harmonious communication both locally and globally in today’s interconnected world.